Principles and strategies to balance ethical, social and environmental concerns with corporate requirements - Leonard, Liam.; Gonzalez-Perez, Maria Alejandra (Bingley, U.K. : Emerald, 2013)
Advances in Sustainability & Environmental Justice Volume 12: Principles and Strategies to Balance Ethical Social and Environmental Concerns with Corporate Requirements brings together a range of practitioners and academics from the world of business who examine corporate social responsibility in policy and practice in a series of case studies from across the globe. This volume, co-edited by Dr. Liam Leonard and Dr. Maria Alejandra Gonzalez-Perez, is the second in the series (formerly Advances in Ecopolitics) dedicated to Corporate Social Responsibility within the scope of international business. Both books in this pair of studies bring together contributions from authors located in 13 countries in the 5 continents, and this second volume on the topic specifically incorporates academic works from 21 researchers representing institutions from Australia, Canada, Colombia, England, Ireland, Kenya, Malaysia, Nigeria, Romania, and the United States. As such, these studies represent one of the most comprehensive collections on contemporary business practices in the significant area of Corporate Social Responsibility.
Introduction / Liam Leonard, Maria Alejandra Gonzalez-Perez -- The corporate paradox : marketing, innovation, corruption and pollution : an overview of corporate successes and failures / Liam Leonard, Maria Alejandra Gonzalez-Perez -- An eclectic review of critical perspectives on globalisation and international business : setting the context for corporate social responsibility and sustainability / Maria Alejandra Gonzalez-Perez -- An analysis on the link between emerging markets MNEs' reputation and corporate social responsibility / Alina Mihaela Dima, Simona Nicoleta Vasilache -- Business, sustainability, and base of the pyramid / Maria Alejandra Pineda-Escobar -- External intrusion, internal tragedy : environmental pollution and multinational corporations in sub-Saharan Africa / Evans S. Osabuohien, Uchenna R. Efobi, Ciliaka M.W. Gitau -- Drivers, trends, and outlook in sustainable development : comparing best practices in Northern Europe (Denmark, Finland, Norway, Sweden) and California / Karina A. Branum ... [et al.] -- The accountability challenge to global e-commerce : the need to overcome the developed-developing country divide in WTO e-commerce policies / Farrokh Farrokhnia, Cameron Keith Richards -- Corporate social responsibility in cyberspace : selling out to autocratic regimes : implications from the case of Google corporation in China / Susan C. Morris -- Ethics, CSR and MNCs : establishing the link with HRM in times of economic crisis / Vlasios Sarantinos -- Corporate ethics and values : guiding business out of the maelstrom / Jane Ross, Jack Ross, Andrew Creed.
Keywords: Business & Economics -- Business Ethics; Business ethics; Sustainability; Business ethics; Social responsibility of business